Vascular Complication in Adolescents With Diabetes Mellitus - Graves, Lara E.; Donaghue, Kim C. (Frontiers in Endocrinology, 2020)
Diabetes mellitus is becoming more prevalent and even with new advancements which improve glycaemic control, complications of diabetes are common. Vascular complications of diabetes include the microvascular complications: retinopathy, nephropathy, and peripheral and autonomic neuropathy. Macrovascular complications are also common in patients with diabetes and arguably more concerning as they confer a high mortality risk yet are sometimes under-treated. Risk factors for diabetes complications start to occur in childhood and adolescents and some youths may be diagnosed with complications before transition to adult care. This article discusses the prevalence, risk factors, screening and treatment recommendations for vascular complications in children and adolescents with diabetes.